ANTICONVULSANT ACTIVITY OF METHANOL LEAF FRACTIONS OF LAGGERA AURITA LINN (ASTERACEAE) IN LABORATORY ANIMALS - Gudaji, Mustapha Ibrahim; Doma, Abdullahi Ibrahim; Malami, Sani (FUDMA JOURNAL OF SCIENCES, 2024)
The Plant Laggera aurita Linn, a widely used medicinal plant in Africa, in the treatment of many medical conditions. This study was conducted to evaluate the anticonvulsant effects of solvents fractions of methanol leaf extract of Laggera aurita in laboratory animals. Phytochemical screening and acute toxicity studies was carried out using standard protocols. The fractions were evaluated against electrically-induced seizures in chicks, pentylenetetrazole induced seizures in mice and pentylenetetrazole kindling in rats. The analysis of the solvents fractions of Laggera aurita revealed alkaloids, flavonoids, tannins, steroids, terpenoids and cardiac glycosides. The i.p median lethal dose values in mice for NHF were found to be 1264mg/kg, 2154mg/kg for EAF and 3807mg/kg for RAF. The maximal electroshock induced seizure model of solvents fractions did not protect the animals against tonic hind limb extension (THLE), however it increases the mean recovery time of the convulsed chicks at all doses tested. In the subcutaneous pentylenetetrazole-induced seizure model, the NHF protected the mice against seizure at all doses tested, up to 50% at 200mg/kg and 400mg/kg, while the EAF and RAF confers no protection against seizures at all doses tested (150mg/kg, 300mg/kg, 600mg/kg for EAF and 250mg/kg, 500mg/kg and 1000mg/kg for RAF). The NHF produced significant protection against subcutaneous pentylenetetrazole (40mg/kg) induced kindling in rats at all the doses tested, while the EAF and RAF shows no protection. The study therefore suggests the presence of bioactive compounds in the plant that posses’ anticonvulsant activity and may be of pharmacological benefit in the management of epilepsy.
Keywords: Anticonvulsant; Laggera aurita; Pentylenetetrazole; Solvent fractions